Pengaruh Income Terhadap Keputusan Investasi Generasi Z Melalui Perilaku Keuangan (Studi Kasus Pada Generasi Z Di Kabupaten Bekasi) - Putranto, Wahyu Tri; Wati, Ratna (Riviera Publishing, 2025)
The purpose of this study is to determine the influence of income on Generation Z's investment decisions through Financial Behavior. The focus of this research is Generation Z, especially in Bekasi Regency. The population used is generation z who live in Bekasi district. The method used to conduct this study is to use Partial Least Square (PLS) using SmartPLS software Version 4.0. The sample was selected based on the lemeshow formula and a sample of 100 respondents was obtained. The sampling method in this study is purposive sampling. The results of the study prove that Income has a significant positive effect on Investment Decisions, Income has a significant positive effect on Financial Behavior, Generational Financial Behavior does not have a positive and significant effect on Investment Decisions and Financial Behavior does not mediate the relationship between Income and Investment Decisions of generation Z in Bekasi Regency.